Effect of Milwaukee Brace on Quality of Life in Adolescents with Idiopathic Scoliosis - Zarea, Mohammad; Aminian, Gholamreza; Khosravi, Mobina; Baghaei, Roshanak (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Scoliosis is defined as a lateral deviation of the normal vertical line of the spine measured on radiography, with the curve greater than 10 degrees. One of the braces commonly used for scoliosis is Milwaukee. The purpose of this study was to evaluate the effect of Milwaukee brace on quality of life (QoL) in adolescents with adolescent idiopathic scoliosis (AIS) using the QLPSD questionnaire. Material and Method: Eighty-four patients (10- 20 years old) with AIS were recruited. Patients divided into two groups: intervention group (with Milwaukee brace) and control group (without any interventions), The "Quality of Life Profile for Spine Deformities" (QLPSD) questionnaire was used to assess the individuals' QoL. The highest score indicates the lowest QoL and the lowest score indicates the highest QoL. The independent t-test was used to evaluate the difference between two groups. Result: There were a significant increase between two groups in total QLPSD score (P=0.015). Regarding the QLPSD dimensions, mental function (P=0.003), sleep disorders (P=0.001), self-image (P=0.016), and flexibility of spine (P=0.018) were increased in Milwaukee brace group compared with no intervention group. Pain differences in two groups was not significant (P=0.061). Conclusion: Using the Milwaukee brace reduced individuals' QoL with AIS. Due to the effective role of QoL on the treatment process, the Milwaukee braces should be prescribed cautiously. Key words: Idiopathic Scoliosis, Milwaukee Brace, Quality of Life, QLPSD Questionnaire